The Effect of Parental Education Level on Student Achievement in Airtiris Public Elementary School - Umi Kalsum; Mhmd Habibi; Risna Wati (Journal of Educational Sciences, 2023)
This study aims to find out the influence of parents' educational level on student achievement at Public Elementary School 001, Air Tiris. The data collection process here involves a combination of techniques between documentation and observation. There are several types of data analysis, two of which are descriptive analysis techniques and inferential analysis techniques. Twenty-four students from 001 Airtiris Public Elementary School were included in this study as research subjects. The results of this study show that there is a relationship between parents' education and student achievement. To ensure their children do well in school, parents must supervise and guide them during their homeschooling. It is suggested that they can help improve their children's achievement. This is due to the fact that research findings show that parents are the most effective educators for their children's academic success. Students who study at home to achieve good academic results.